2006
DOI: 10.1002/mop.22008
|View full text |Cite
|
Sign up to set email alerts
|

Further comments on the performances of finite element simulators for the solution of electromagnetic problems involving metamaterials

Abstract: In this paper, we analyze the performances of three‐dimensional finite element (FE) simulators in handling electromagnetic scattering problems involving metamaterials. It has already been proved that the performances of the FE method are worse than usual, when metamaterials are considered. In this work, we extend our previous analysis by providing some additional results on the precision of the FE solution and on the performances of the iterative and direct solvers typically used with FE simulators. © 2006 Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Indeed, it has been recently demonstrated that waveguide discontinuity problems can become ill-posed even in the presence of lossy media and absorbing boundary conditions [23]. Consequently, several anomalies of the numerical reliability of existing numerical methods, such as the FE 3, have been pointed out in canonical direct scattering problems involving effective MTM s [22,25,31].…”
Section: Mathematical Formulation and Previous Results On Fe And Fdfdmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, it has been recently demonstrated that waveguide discontinuity problems can become ill-posed even in the presence of lossy media and absorbing boundary conditions [23]. Consequently, several anomalies of the numerical reliability of existing numerical methods, such as the FE 3, have been pointed out in canonical direct scattering problems involving effective MTM s [22,25,31].…”
Section: Mathematical Formulation and Previous Results On Fe And Fdfdmentioning
confidence: 99%
“…In particular, the presence of complementary or almost complementary MTM s has shown to deeply affect the accuracy of the FE solutions and the convergence rate of some popular iterative solver used for the solution of the associated linear systems [22,25,31]. Accordingly, such preliminary conclusions [22,25,31] have suggested that FE method could have some intrinsic characteristics which make it particularly sensitive to the anomalies of MTM models.…”
Section: Mathematical Formulation and Previous Results On Fe And Fdfdmentioning
confidence: 99%
See 3 more Smart Citations